The Impact of Autonomous Vehicles in Parcel Industry in Kedah - Maniam, Saroja; Che Rusuli, Muhamad Saufi; Abu Yaziz@Mohamad, Mohd Fathi; Che Hussin, Kasmaruddin; Wan Mohd Nasir, Wan Mohd Nazdrol; Che Hussin, Kasmaruddin (Research in Management of Technology and Business, 2022)
Autonomous vehicles are promising vital advantages for parcel industry that facing obstacles with growing labor shortage and the demand increases to deliver in short time period. Marketers have found that consumers increasingly prefer a product that be deliver on time with faster time period by the parcel sectors. This study eager to know the impact of autonomous vehicles especially in parcel activities. There were 251 consumers who have been involve as respondents in this study. As such, the finding indicates that all hypotheses are accepted and meet the objectives of the study. This study is expected to provide readers with an understanding of the packaging industry, the technology used and its autonomous vehicle activities in ensuring the sustainability in the industry.